2001
DOI: 10.2741/chan
|View full text |Cite
|
Sign up to set email alerts
|

Gene targeting in hemostasis. tissue factor pathway inhibitor

Abstract: Factor VII (FVII), in concert with its natural cofactor and receptor, Tissue Factor (TF), initiates the process of blood coagulation following vascular injury. Mice completely deficient in FVII were generated via specific deletion of exons 2 to 8, thus deleting the entire coding region of the mature protein. In contrast to the early lethality observed in TF-deficient embryos (TF-/-), embryos deficient in FVII (FVII-/-) developed normally, without incidence of hemorrhage. However, FVII-/- neonates succumbed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Experiments on genetically modified mice with TFPI gene disruption showed that they die prematurely in embryonic stage and before birth due to haemorrhagic and intravascular thrombi. Human embryos with TFPI deficiency may suffer a similar problem and this may explain why no cases with TFPI deficiency has been identified so far (Broze, 1998;Chan, 2001;Maroney & Mast;2008).…”
Section: Tissue Factor Pathway Inhibitor (Tfpi) Deficiencymentioning
confidence: 99%
“…Experiments on genetically modified mice with TFPI gene disruption showed that they die prematurely in embryonic stage and before birth due to haemorrhagic and intravascular thrombi. Human embryos with TFPI deficiency may suffer a similar problem and this may explain why no cases with TFPI deficiency has been identified so far (Broze, 1998;Chan, 2001;Maroney & Mast;2008).…”
Section: Tissue Factor Pathway Inhibitor (Tfpi) Deficiencymentioning
confidence: 99%